Isolation, Evaluation, and Identification of Angiotensin I-Converting Enzyme Inhibitory Peptides from Game Meat - Takeda, Shiro; Kaneko, Sakurako; Sogawa, Kazuyuki; Ahhmed, Abdulatef M.; Enomoto, Hirofumi; Kawarai, Shinpei; Taira, Kensuke; Mizunoya, Wataru; Minami, Masato; Sakata, Ryoichi (MDPI, 2020)
Game meat has been underutilized, while it offers the potential to diversify not only the human diet but also increase food production and the nutritional value of meat products. This study aimed to determine the angiotensin I-converting enzyme (ACE) inhibitory activities of the digested game meats (venison and boar meat) compared with those of livestock meats (beef and pork). Through the sodium dodecyl sulfate polyacrylamide gel electrophoresis and size chromatography results, we found that the digested products from each meat had different molecular weights. The ACE inhibitory ratio in all tested samples had gradually increased following by the enzyme treatments. ACE inhibitory ratios and the half maximal inhibitory concentration values indicated that digested venison was the most potent inhibitor of ACE activity, followed by the digested boar meat. The level of anserine in digested venison was higher than that in the other meats, but the carnosine level was lower. Through fractionations and liquid chromatography-tandem mass spectrometry analysis, five ACE inhibitory peptides were identified from the digested venison. Of these peptides, Isoleucine-Lysine- Glutamic Acid-Valine-Threonine-Glutamic Acid-Arginine (IKEVTER) demonstrated the highest ACE inhibitory activity. Therefore, the game meat is food that is believed potentially to offer high bioactivities, particularly antihypertensive forces.
Keywords: venison; angiotensin I-converting enzyme (ACE) inhibitory activity; game meat; bioactive peptide; boar meat; gastrointestinal digestion; VITRO GASTROINTESTINAL DIGESTION; BIOACTIVE PEPTIDES; CHICKEN; MUSCLE; BEEF; PORK; PRODUCTS; ANTIOXIDANT; CARNOSINE; Food Science & Technology